Reconfiguration Management in the Context of RTOS-Based HW/SW Embedded Systems. (20th November 2007) - Eustache, Yvan; Diguet, Jean-Philippe
Abstract : This paper presents a safe and efficient solution to manage asynchronous configurations of dynamically reconfigurable systems-on-chip. We first define our unified RTOS-based framework for HW/SW task communication and configuration management. Then three issues are discussed and solutions are given: the formalization of configuration space modeling including its different dimensions, the synchronization of configuration that mainly addresses the question of task configuration ordering, and the configuration coherency that solves the way a task accepts a new configuration. Finally, we present the global method and give some implementation figures from a smart camera case study.